Medbesedilne povezave med Slávy dcero Jana Kollárja in Djulabijami Stanka Vraza - Jež, Andraž (Slavistična revija, 2013)
The article focuses on several intertextual connections between the opuses of the Slovak Pan-Slavist Ján Kollár and the Slovene-Croatian Illyrian poet Stanko Vraz, more specifically,on themulti-layered influence that Kollárs epic poem Slávy dcera had on Vraz's first book of poems written in the new Illyrian language, Djulabije. The first part outlines Vrazs complex links with Czech culture, which he considered to be most prestigious and central to the question of Slavic national revival. In the second part, the article is centered around the elements of Kollárs work that most inspired Vraz. The last part provides analyses of both literary works, the earlier of which is a very complex case of intertextuality in itself.
Keywords: "Djulabije"; "Sláva dcera"; Croatian literature; Czech literature; češka književnost; hrvaška književnost; ilirizem; Illyrian movement; intertekstualnost; intertextuality; Kollár, Jan, 1793-1852; narodni preporod; Pan-Slavism; panslavizem; Slavic national revivals; Vraz, Stanko, 1810-1851